Altered Surfactant Protein Expression in Primary Acquired Nasolacrimal Duct Obstruction - Mohammad, Javed Ali; Bráuer, Lars; Schicht, Martin; Paulsen, Friedrich (Ophthalmic Plastic and Reconstructive Surgery, 2019)
PURPOSE: To investigate the presence and distribution patterns of 6 surfactant proteins in lacrimal drainage tissues of patients with primary acquired nasolacrimal duct (NLD) obstruction. METHODS: The presence and distribution of surfactant proteins (SP)-G and SP-H was first assessed in normal cadaveric lacrimal systems. The study was then performed in 10 samples of lacrimal sac and the respective NLDs obtained from patients suffering from primary acquired NLD obstruction who underwent either a dacryocystorhinostomy or a dacryocystectomy. The lacrimal sac samples were further divided into fundus and body, soon after their removal. Immunohistochemical labeling was performed for assessing the presence and distribution of SPs: SP-A, SP-B, SP-C, SP-D, SP-G/SFTA2, and SP-H/SFTA3. The results were then scored as positive or negative and the distribution pattern, if any, within the lacrimal sac and NLDs was assessed. Human lung tissues were used as controls. RESULTS: SP-H was demonstrated in the lining epithelia of the normal lacrimal drainage systems, whereas SP-G was uniformly negative. Immunohistochemical labeling revealed wide variations in the staining patterns of different SPs in different regions of the lacrimal sac and the NLD. SP-D and SP-G revealed uniformly negative immunoreactivity. Variable staining patterns were also noted between the superficial and basal layers of the lining epithelia. However, the goblet cells and intraepithelial mucous glands did not express any of the SPs. CONCLUSIONS: This study provides a proof of principle for the presence of SP-H and absence of SP-G in the normal lacrimal drainage systems. In cases of primary acquired nasolacrimal duct obstruction, there were alterations or loss of SP expression in the lining epithelia of the lacrimal sac and NLDs, reflecting their possible role in the etiopathogenesis of primary acquired nasolacrimal duct obstruction.In cases of primary-acquired nasolacrimal duct obstruction, the expression of multiple surfactant proteins was either deranged or lost in the lining epithelium of the lacrimal sac and nasolacrimal ducts.
CRIS-Team Scopus Importer:2019-11-15